2014
DOI: 10.1016/j.celrep.2014.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Plac8 Links Oncogenic Mutations to Regulation of Autophagy and Is Critical to Pancreatic Cancer Progression

Abstract: Summary Mutations in p53 and RAS potently cooperate in oncogenic transformation and correspondingly these genetic alterations frequently coexist in pancreatic ductal adenocarcinoma (PDA) and other human cancers. Previously we identified a set of genes synergistically activated by combined RAS and p53 mutations as frequent downstream mediators of tumorigenesis. Here, we show that the synergistically activated gene Plac8 is critical for pancreatic cancer growth. Silencing of Plac8 in cell lines suppresses tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 67 publications
5
86
3
Order By: Relevance
“…Oncogenic p53 and Ras mutations cooperate to induce many transformation-specific phenotypes (Kinsey et al, 2014; McMurray et al, 2008; Smith and Land, 2012; Xia and Land, 2007), and, accordingly, many of the metabolic phenotypes observed here were cooperatively induced (Figure 1K). However, a number of these metabolic activities were induced predominately by expression of either mp53 or oncogenic Ras.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Oncogenic p53 and Ras mutations cooperate to induce many transformation-specific phenotypes (Kinsey et al, 2014; McMurray et al, 2008; Smith and Land, 2012; Xia and Land, 2007), and, accordingly, many of the metabolic phenotypes observed here were cooperatively induced (Figure 1K). However, a number of these metabolic activities were induced predominately by expression of either mp53 or oncogenic Ras.…”
Section: Resultsmentioning
confidence: 76%
“…It remains unclear, however, at what point of the multi-step process of carcinogenesis the glycolytic phenotype emerges and whether this transition is driven by cell-intrinsic mechanisms or by selective forces in the cancer microenvironment (e.g., oxygen limitation). We have extensively used young adult murine colon (YAMC) cells (Whitehead et al, 1993) transduced with activated Ras and mutant p53 to investigate the molecular mechanisms underlying the cooperative nature of malignant cell transformation, which has revealed cancer cell-specific vulnerabilities relevant to human disease (Kinsey et al, 2014; McMurray et al, 2008; Smith and Land, 2012; Xia and Land, 2007; Experimental Procedures). This model is therefore well suited to investigate the metabolic changes associated with the transition to malignancy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The top identified genes were then further selected for their relevance to cancer and are depicted in Supplementary Table 1. Among the genes downregulated after NFAT1 silencing were follistatin (FST), which has been reported as a contributor to bone metastasis (16), and placenta-specific 8 (PLAC8), whose overexpression has been reported to protect cancer cells from apoptosis (17-19). Downregulation was also observed in the frizzeld family receptor 4 (FZD4) and the nicotinamide N-methyltransferase (NNMT) genes.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report by Kinsey and colleagues (36) suggested that PLAC8 expression promotes tumor progression in epithelial tumors (including pancreatic cancer) via autophagy-related mechanisms. Our own results, however, clearly exclude autophagy-related functions of PLAC8 in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%